Clonal Relatedness of Enterotoxigenic Escherichia coli Strains Isolated from a Cohort of Young Children in Guinea-Bissau - Steinsland, Hans (American Society for Microbiology, 2004)
In a cohort study of 200 young children in Guinea-Bissau, it was previously found that some enterotoxigenic Escherichia coli (ETEC) strains were more pathogenic than others, depending on the type of toxin that they could produce, and that natural ETEC infections induced substantial protection against new infections with ETEC strains that had the same combination of toxins and colonization factors (CFs). We wanted to describe the clonal relatedness of the ETEC strains isolated during this study and to investigate whether the protective antigens and the virulence factors that were responsible for the pathogenic traits were common to strains that were clonally closely related or whether they were more likely to be encoded by the ETEC virulence plasmids that normally encode the toxins and the CFs. By performing repetitive sequence-based PCR analysis of strains representing 452 infections, we found that strains that had the same toxin-CF profile were usually closely related, although a few were unrelated. Strains that did not have the same toxin-CF profiles but that were positive for a given toxin or for a given CF were not consistently more closely related to each other than to strains that were negative for the same toxin or CF. Our results indicate that the pathogenic traits of ETEC were mainly attributed to genes carried on the ETEC virulence plasmids. Because most strains that had the same toxin-CF profile were closely related, it seems likely that the toxin-CF-specific protection was clonal and was not targeting antigens encoded by the virulence plasmids. These results are of relevance to the ETEC vaccine development effort.